2017
DOI: 10.4103/jmh.jmh_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Current practices for treatment of uterine fibroids

Abstract: The treatment of uterine fibroids depends on symptoms of patients, size of the fibroid, desire for future pregnancy, and preference of the treating gynecologist. The present study was undertaken to compare treatment preferences in women desirous and nondesirous of pregnancy by an experienced gynecologist in symptomatic uterine fibroids. Newer medical or minimally invasive treatment modalities are increasingly being used for the treatment of fibroids. However, conventional surgical treatment such as myomectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…When symptom-atic, their management mainly involves surgery, which is all too often radical (hysterectomy). 4,5 Homoeopathic treatment has indicated positive results in the treatment of fibroid as Popov's study shows that homoeopathic medicines can help patient symptomatically not only control pain and abnormal endometrial bleeding but also reduce the size and stop the growth of the tumour. 6 Iqbal et al 7 in their cohort study and case reports like Rath et al 8 and Sever et al 9 showed positive result in reduction and resolution of uterine fibroids.…”
Section: Introductionmentioning
confidence: 99%
“…When symptom-atic, their management mainly involves surgery, which is all too often radical (hysterectomy). 4,5 Homoeopathic treatment has indicated positive results in the treatment of fibroid as Popov's study shows that homoeopathic medicines can help patient symptomatically not only control pain and abnormal endometrial bleeding but also reduce the size and stop the growth of the tumour. 6 Iqbal et al 7 in their cohort study and case reports like Rath et al 8 and Sever et al 9 showed positive result in reduction and resolution of uterine fibroids.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy has long been considered the treatment of choice for symptomatic uterine leiomyoma (ULM), despite the consequences on fertility in women of reproductive age. [ 1 ] Nowadays, minimally invasive surgical approaches such as myomectomy through the laparoscopic or the hysteroscopic route, mini-invasive laparotomy, and robotic assisted surgery are more often proposed especially in women who wish to preserve their fertility. [ 2 ] Power morcellation represents a useful approach that facilitates minimally invasive surgery of even large uterine masses.…”
Section: Introductionmentioning
confidence: 99%